2016
DOI: 10.1016/j.envres.2016.07.002
|View full text |Cite
|
Sign up to set email alerts
|

Phenols and parabens in relation to reproductive and thyroid hormones in pregnant women

Abstract: Introduction Phenols and parabens are ubiquitous environmental contaminants. Evidence from animal studies and limited human data suggest they may be endocrine disruptors. In the current study, we examined associations of phenols and parabens with reproductive and thyroid hormones in 106 pregnant women recruited for the prospective cohort, “Puerto Rico Testsite for Exploring Contamination Threats (PROTECT)”. Methods Urinary exposure biomarkers (bisphenol A, triclosan, benzophenone-3, 2,4-dichlorophenol, 2,5-d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
101
5
8

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 164 publications
(122 citation statements)
references
References 55 publications
8
101
5
8
Order By: Relevance
“…For example, Aker et al (2016) used data from a cohort study of pregnant women in Puerto Rico to examine associations between urinary TCS concentrations measured during three visits at [16][17][18][19][20][20][21][22][23][24], and 24-28 weeks gestation and serum levels of thyroid and sex hormones at visits 1 and 3.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…For example, Aker et al (2016) used data from a cohort study of pregnant women in Puerto Rico to examine associations between urinary TCS concentrations measured during three visits at [16][17][18][19][20][20][21][22][23][24], and 24-28 weeks gestation and serum levels of thyroid and sex hormones at visits 1 and 3.…”
Section: Discussionmentioning
confidence: 99%
“…Tier 2 included 13 publications. Twelve of those publications (Wolff et al , 2010(Wolff et al , 2015Philippat et al 2012Philippat et al , 2014Watkins et al 2015;Aker et al 2016;Ashley-Martin et al 2016;Buckley et al 2016;Lassen et al 2016;Smarr et al 2017;Geer et al 2017) were based on seven different cohorts assembled in France, Puerto Rico, Denmark, Canada, and various parts of the US. One paper ) presented a case-control study that used incident cases identified among members of a French cohort.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations